Vitamin D Deficiency Among Healthy Infants - Muhammad Waqas Ashfaq , Rai Muhammad Asghar , Saba Naim Khan (Journal of Rawalpindi Medical College, 2014)
Background: To determine the frequency of Vitamin D deficiency in healthy infants in order to prevent Rickets and other conditions associated with it. Methods: In this Cross Sectional Study, total 72 healthy infants of age 09 months to 12 months were selected .Blood sample (3ml) was also collected for quantitative determination of 25-hydroxy vitamin D level,by Enzyme immunoassay. X-ray wrists were done of Vitamin D deficient infants. Results: 25-hydroxy vitamin D level were found suboptimal in 50%,deficient in 15.3 and deverly deficient in 2.8%.Radiological studies of the wrists were conducted in infants having below suboptimal serum 25-hydroxy vitamin D level which showed that 53.8% of the patients had radiological findings suggestive of Rickets and 46.2% were normal. Conclusion:Serum 25-hydroxy Vitamin D concentration was low in otherwise healthy infants. Vitamin D supplementation should be started early in infancy